2008
DOI: 10.1063/1.2929841
|View full text |Cite
|
Sign up to set email alerts
|

How noise statistics impact models of enzyme cycles

Abstract: Theoretical tools for adequately treating stochastic effects are important for understanding their role in biological processes. Although master equations provide rigorous means for investigating effects associated with fluctuations of discrete molecular copy numbers, they can be very challenging to treat analytically and numerically. Approaches based on the Langevin approximation are often more tractable, but care must be used to ensure that it is justified in each situation. Here, we examine a model of an en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…One application of our mathematical results was to models of single or communicating "toggle switches" in bacteria, where we showed that, for suitable parameters, there are a very large number of metastable attractors. Indeed, stochastic effects have been shown before to lead to multi-stability in a population of enzymatic reactions [73].…”
Section: Discussionmentioning
confidence: 99%
“…One application of our mathematical results was to models of single or communicating "toggle switches" in bacteria, where we showed that, for suitable parameters, there are a very large number of metastable attractors. Indeed, stochastic effects have been shown before to lead to multi-stability in a population of enzymatic reactions [73].…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical studies predict that multiplicative noise can introduce bifurcations in systems that are monostable for all parameter ranges (17,(19)(20)(21)(22) (26)(27)(28)(29)(30)(31). In this paper, we refer only to one of the hypothesized sources of transcriptional pulsing; namely, the discrete random binding/ unbinding of TFs.…”
mentioning
confidence: 99%
“…The enzymatic futile cycle is a simple and robust model that can, in certain parameter regimes, exhibit qualitatively different behavior due to stochastic noise [59,60]. This signaling motif can be seen in biological systems including GTPase cycles, MAPK cascades, and glucose mobilization [59,61,62].…”
Section: Modelmentioning
confidence: 99%